Glucose 6-phosphate dehydrogenase 6-phosphogluconolactonase: characterization of the Plasmodium vivax enzyme and inhibitor studies - Kristina Haeussler; Isabell Berneburg; Esther Jortzik; Julia Hahn; Mahsa Rahbari; Norma Schulz; Janina Preuss; Viktor A. Zapol’skii; Lars Bode; Anthony B. Pinkerton; Dieter E. Kaufmann; Stefan Rahlfs; et al. (Malaria Journal, 2019)
Abstract Background Since malaria parasites highly depend on ribose 5-phosphate for DNA and RNA synthesis and on NADPH as a source of reducing equivalents, the pentose phosphate pathway (PPP) is considered an excellent anti-malarial drug target. In Plasmodium, a bifunctional enzyme named glucose 6-phosphate dehydrogenase 6-phosphogluconolactonase (GluPho) catalyzes the first two steps of the PPP. PfGluPho has been shown to be essential for the growth of blood stage Plasmodium falciparum parasites. Methods Plasmodium vivax glucose 6-phosphate dehydrogenase (PvG6PD) was cloned, recombinantly produced in Escherichia coli, purified, and characterized via enzyme kinetics and inhibitor studies. The effects of post-translational cysteine modifications were assessed via western blotting and enzyme activity assays. Genetically encoded probes were employed to study the effects of G6PD inhibitors on the cytosolic redox potential of Plasmodium. Results Here the recombinant production and characterization of PvG6PD, the C-terminal and NADPH-producing part of PvGluPho, is described. A comparison with PfG6PD (the NADPH-producing part of PfGluPho) indicates that the P. vivax enzyme has higher K M values for the substrate and cofactor. Like the P. falciparum enzyme, PvG6PD is hardly affected by S-glutathionylation and moderately by S-nitrosation. Since there are several naturally occurring variants of PfGluPho, the impact of these mutations on the kinetic properties of the enzyme was analysed. Notably, in contrast to many human G6PD variants, the mutations resulted in only minor changes in enzyme activity. Moreover, nanomolar IC50 values of several compounds were determined on P. vivax G6PD (including ellagic acid, flavellagic acid, and coruleoellagic acid), inhibitors that had been previously characterized on PfGluPho. ML304, a recently developed PfGluPho inhibitor, was verified to also be active on PvG6PD. Using genetically encoded probes, ML304 was confirmed to disturb the cytosolic glutathione-dependent redox potential of P. falciparum blood stage parasites. Finally, a new series of novel small molecules with the potential to inhibit the falciparum and vivax enzymes were synthesized, resulting in two compounds with nanomolar activity. Conclusion The characterization of PvG6PD makes this enzyme accessible to further drug discovery activities. In contrast to naturally occurring G6PD variants in the human host that can alter the kinetic properties of the enzyme and thus the redox homeostasis of the cells, the naturally occurring PfGluPho variants studied here are unlikely to have a major impact on the parasites’ redox homeostasis. Several classes of inhibitors have been successfully tested and are presently being followed up.